Alternative redo sternotomy in a patient with tracheostoma and patent grafts. (September 2014) - Uehara, Kyokun; Minakata, Kenji; Funamoto, Masaki; Yamazaki, Kazuhiro; Marui, Akira; Sakata, Ryuzo
We describe a redo mitral valve replacement operation in a 71-year-old man with a tracheostoma and patent bypass grafts to the coronary arteries. Preoperative investigations revealed that the patent right internal thoracic artery graft ran directly under the sternum just anterior to the ascending aorta, and a saphenous vein graft was adhering to a surgical wire. To prevent injury to the patent grafts and cardiac structures, and to avoid communication with the tracheostoma, the redo procedure was performed via an anterior minithoracotomy combined with a low T-shaped partial sternotomy. The reoperation was successfully completed without any complications.